A walk in the woods - Bryson, Bill.; Cook, David (London : Black Swan, 1998)
Author Bill Bryson provides an account of his experiences hiking the Appalachian Trail with a childhood friend, telling of how they survived a blizzard, got lost, and had encounters with eccentric characters, and rude yuppies along the way.
Adult.
Adult
Keywords: Bryson, Bill -- Travel -- Appalachian Trail; Bryson, Bill -- Travel; Natural history -- Appalachian Trail; Natural history -- Appalachian Trail; Appalachian Trail -- Description and travel; Appalachian Trail -- Description and travel